The puzzling world of Winston Breen - Berlin, Eric. (New York, N.Y. : G.P. Putnam's Sons, 2007)
Puzzle-crazy, twelve-year-old Winston and his ten-year-old sister Katie find themselves involved in a dangerous mystery involving a hidden ring. Puzzles for the reader to solve are included throughout the text.
670
Keywords: Brothers and sisters -- Juvenile fiction; Puzzles -- Juvenile fiction; Mystery fiction